PENERAPAN KURIKULUM MERDEKA DI SEKOLAH DASAR NEGERI 21 TELUK PAKEDAI - Mayasari, Tika; Hairida, Hairida; Muhairini, Rini (Jurnal Visi Ilmu Pendidikan, 2025)
This research is motivated by the existence of regulations from the Ministry of Education and Culture-Research and Technology regarding the implementation of the Independent Curriculum which is still facing various challenges in the field. Many teachers have difficulty understanding, implementing, and evaluating this curriculum optimally. This study aims to describe the implementation of the independent curriculum at SDN 21 Teluk Pakedai. This research uses a qualitative method that will be carried out in May 2025 with the subjects of school principals, teachers, and grade IV students. Data was obtained through observation, interviews, and documentation. The results of the study show that SDN 21 Teluk Pakedai has implemented the Independent Curriculum since the 2022/2023 Academic Year. Teachers have difficulties in compiling teaching modules and the use of technology, but try to overcome them by looking for references and attending training regularly.